Notch signaling regulates pulmonary fibrosis - Zhang, Xinyue; Xu, Zhihao; Chen, Qi; Zhou, Zhimin (Frontiers in Cell and Developmental Biology, 2024)
Pulmonary fibrosis is a progressive interstitial lung disease associated with aging. The pathogenesis of pulmonary fibrosis remains unclear,however, alveolar epithelial cell injury, myofibroblast activation, and extracellular matrix(ECM) accumulation are recognized as key contributors.Moreover, recent studies have implicated cellular senescence, endothelial-mesenchymal transition (EndMT), and epigenetic modifications in the pathogenesis of fibrotic diseases. Various signaling pathways regulate pulmonary fibrosis, including the TGF-β, Notch, Wnt, Hedgehog, and mTOR pathways. Among these, the TGF-β pathway is extensively studied, while the Notch pathway has emerged as a recent research focus. The Notch pathway influences the fibrotic process by modulating immune cell differentiation (e.g., macrophages, lymphocytes), inhibiting autophagy, and promoting interstitial transformation. Consequently, inhibiting Notch signaling represents a promising approach to mitigating pulmonary fibrosis. In this review, we discuss the role of Notch signaling pathway in pulmonary fibrosis, aiming to offer insights for future therapeutic investigations. 1 Pulmonary Fibrosis Represents a Central Feature of Interstitial Lung Diseases Interstitial lung diseases (ILDs) are a heterogeneous group of respiratory diseases, which often result in varying degrees of pulmonary fibrosis and respiratory dysfunction. Despite numerous estimated causative factors, the etiology of ILDs remains unclear. Pulmonary fibrosis, a primary characteristic of ILD, arises from an exaggerated cascade of inflammatory and reparative responses within the pulmonary interstitium. This cascade, initiated by diverse disease factors, leads to structural remodeling of lung tissue ,excessive deposition of extracellular matrix , and ultimately fibrosis formation(Distler et al., 2019). Fibrosis progresses to dyspnea and lung failure, often resulting in a high mortality rate. Idiopathic pulmonary fibrosis (IPF) represents the most prevalent form of fibrosing ILD. Clinically, patients typically present with respiratory symptoms, including cough and exertional dyspnea, which progress to deterioration of lung function. Imaging and pathological findings closely resemble those of usual interstitial pneumonia (UIP)(Inui et al., 2021). IPF primarily affects middle-aged and older adults, typically manifesting in the sixth and seventh decades of life,with an incidence that escalates significantly with age (King et al., 2011;Raghu et al., 2011;